Case report: Multiple brain tuberculomas after in vitro fertilization, embryo transfer, and abortion - Shi, Zhaobo; Sun, Yong (Frontiers in Neurology, 2022)
Abstract Background Multiple brain tuberculomas (MBT), characterized by disseminated tuberculous granulomas in the brain, is a rare disease like tuberculosis after in vitro fertilization, embryo transfer (IVF-ET) and abortion. This study aimed to investigate the clinical characteristics, diagnostic methods and therapeutic strategies of MBT after IVF-ET and abortion. Methods A retrospective analysis was performed on the data of two patients suffered from MBT after IVF-ET and abortion. Results Both patients manifested with headache and vomiting, which are the common symptoms of intracranial hypertension, accompanied by tuberculous meningitis. Besides, case 1 was affected by fever and epilepsy. In terms of imaging characteristics, T2-weighted imaging (T2WI) displayed multiple intracranial punctate or patchy high-intensity signals, some of which were presented as “target sign” or enhanced like disseminated nodules, similar to miliary tuberculosis. Regular anti-tuberculosis therapy with isoniazid, rifampicin, pyrazinamide, and ethambutol was administered, but failed to achieve significant effect in the initial stage. The symptoms were gradually relieved and the brain lesions in MRI were significantly alleviated after combining with intrathecal injections of isoniazid, dexamethasone and chymotrypsin. Conclusions IVF-ET may be a risk factor for MBT, the common manifestations of which are intracranial hypertension. In addition to multiple nodular enhancement on brain MRI, the “target sign” on T2WI is likely to be another typical feature of MBT. Provided that there is no obvious effect of regular anti-tuberculosis therapy (ATT), intrathecal injections of isoniazid, dexamethasone and chymotrypsin are considered to produce favorable prognosis, but further studies are still needed to confirm the efficacy.